The Effect of Antibacterial Particle Incorporation on the Mechanical Properties, Biodegradability, and Biocompatibility of PLA and PHBV Composites - Mazur, Karolina; Singh, Raminder; Friedrich, Ralf P.; Genc, Hatice; Unterweger, Harald; Sałasińska, Kamila; Bogucki, Rafał; Kuciel, Stanisław; Cicha, Iwona (Macromolecular Materials and Engineering, 2020)
The composites based on polylactide (PLA) and poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) with the addition of antibacterial particles: silver (Ag) and copper oxide (CuO) are characterized. Basic mechanical properties and biodegradation processes, as well as biocompatibility of materials with human cells are determined. The addition of Ag or CuO to the polymers do not significantly affect their mechanical properties, flammability, or biodegradation rate. However, several differences between the base materials are observed. PLA-based composites have higher tensile and impact strength values, while PHBV-based ones have a higher modulus of elasticity, as well as better mechanical properties at elevated temperatures. Concerning biocompatibility, each of the tested materials support the growth of fibroblasts over time, although large differences are observed in the initial cell attachment. The analysis of hydrolytic degradation effects on the structure of materials shows that PHBV degrades much faster than PLA. The results of this study confirm the good potential of the investigated biodegradable polymer composites with antibacterial particles for future biomedical applications.
CRIS-Team Scopus Importer:2020-08-14
Keywords: biocompatibility; biocomposites; copper oxide particles; poly (3-hydroxybutyrate-co-3-hydroxyvalerate); polylactide; silver particles